Managerial Leadership of the Principal in Improving Teacher Quality: A Multi-Case Study at State Senior High School 1 Ambalawi and Darul Husna Senior High School Ambalawi, Bima Regency - Aldin, Aldin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study examines the principal's managerial leadership in improving teacher quality at SMAN 1 Ambalawi and SMA Darul Husna Ambalawi through a structured and practical needs-based approach. This research is motivated by the importance of principal leadership in improving teacher quality to create quality education. This study aims to describe planning in improving teacher quality in principal leadership at SMAN 1 Ambalawi and SMA Darul Husna Ambalawi. This study uses a qualitative method with a multi-case study approach to describe the principal's managerial leadership in improving teacher quality at SMA Negeri 1 Ambalawi and SMA Darul Husna Ambalawi, Bima Regency. Data were obtained through observation, interviews, and documentation. Analyzed using data condensation techniques, data display, and conclusions. Triangulation was used to validate the validity of the data. The results showed that principals focused on planning to improve teacher quality through needs identification, training, supervision, and the application of a collaborative approach. Training programs involving technology, creative methods, and professional workshops, as well as open communication and awards for outstanding teachers, contributed to the continuous improvement of teacher competence. The principal acts as a facilitator by providing motivation and constructive feedback, creating a work environment that supports innovation and learning. The leadership strategies implemented play a crucial role in building a productive and sustainable learning culture.